2014
DOI: 10.12669/pjms.304.5069
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of Saudi mothers towards their preschool children’s oral health

Abstract: Objectives: To determine knowledge and attitude of Saudi mothers towards their preschool children’s oral health. Methods: One hundred and one mothers (of children aged 16 to 40 months) attending well-baby clinics at Security Forces Hospital Polyclinics in Makkah Al-Mukarrama participated in the study. A questionnaire was used to collect the required information. Results: A great majority (92.1%) of the mothers agreed that “baby teeth are impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Parents play an important role in promoting positive attitudes and strategies toward oral health behaviours [27,28]. Mothers are the immediate and reliable caregivers of children in many countries, and they have a central role in providing effective guidance and positive attitudes toward oral health [29,30]. In the present study, mother's educational level and mother's perception about child's oral health entered in the final and fully adjusted model, however they were not statistically significant.…”
Section: Discussioncontrasting
confidence: 61%
“…Parents play an important role in promoting positive attitudes and strategies toward oral health behaviours [27,28]. Mothers are the immediate and reliable caregivers of children in many countries, and they have a central role in providing effective guidance and positive attitudes toward oral health [29,30]. In the present study, mother's educational level and mother's perception about child's oral health entered in the final and fully adjusted model, however they were not statistically significant.…”
Section: Discussioncontrasting
confidence: 61%
“…Parents are the primary decision makers for children and the first role models. Therefore, their oral health knowledge, a tude and prac ces as well as habits influence their [3][4][5][6][7] children. Apprecia ng and exploring the parental percep on about their children oral health may help the dental community understand some of the reasons why 1,6 children do not receive the dental care they need.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] This is in contrast to findings from pediatric clinics (well-baby clinics) of Security Forces Hospital in Makkah Al-Mukarrama that showed more than half of the mothers (54.5%) agreed that letting baby sleep with bottle still in the mouth was of no harm to teeth. [ 21 ] Similar low levels of knowledge on the role of nocturnal bottle feeding was noted in a study in Addis Ababa, Ethiopia that showed only 25% of mothers were aware that nocturnal bottle feeding may increase risk of dental caries. [ 22 ] The relatively better knowledge in our study participants could be attributed to the promotion of exclusive breastfeeding at clinics during antenatal care, the provision of information on bottle hygiene and the risks associated with prolonged bottle feeding.…”
Section: Discussionmentioning
confidence: 60%